Role of ETT to diagnose coronary artery disease. - Debnath, RC; Siddique, MA; Haque, SS; Banerjee, SK; Ahmed, CM; Mahmood, M; Rahman, MM; Habib, SM; Alam, MS (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):600-4 The abstract of this article is available on the PubMed website